Quality Education: Students’ Willingness towards Professional Courses - Singh, Bharti (Gyan Management Journal, 2018)
Education system in any society is the foundation of the society and key to future. If the Quality education is focused upon with determination then the future of the nation can be secured. The biggest question that arisesishow it can be achieved? There are number of ways to achieve quality education, out of which one is to know the interest of the students and provide them the education in that aspect to ensure quality. The present study, with the help of primary data focuses to know the interest of the students towards various professions and professional courses after passing their 12th class. The study has been conducted with the sample size o/300 students who havejust passed their 12th class or studying in 12th class. They were asked tci tell their preferences towards professions they want to join as carrier, such as Armed forces, doctor, engineer, police, civil services, bank, private industry, own family business, entrepreneur, beauty pageant, boutique, radio jockey,journalists,film industry and any other. Further the respondents were asked to tell their interests to join the course/degree after their 12th from the given options and they were also asked about their preferences towards various streams of Bachelor of Vocations. The present study focuses to conclude most desired profession, most desired program after 12th and most desired Vocational course by the new generation or by the potential students in the degree courses.